SWOT Analysis as the Basis for Formulating PT. Mitra Angsana's Business Strategy in Facing Competition in the Pharmaceutical and Medical Device Distribution Industry - Mala, Santi; Adriyani, Defi; Maulina, Laely (Dinasti International Journal of Management Science, 2025)
Competition in the pharmaceutical and medical device distribution industry is increasingly fierce, requiring companies to formulate effective business strategies. This study aims to analyze the strengths, weaknesses, opportunities, and threats of PT. Mitra Angsana through a SWOT approach, and formulate appropriate business strategies to increase competitiveness. This study uses a descriptive qualitative method with data collection through the study of internal company documents, interviews with management, and analysis of external market information. The results of the analysis indicate that PT. Mitra Angsana has strengths in its extensive distribution network and corporate reputation, but faces weaknesses in the form of limited information technology and human resources. Externally, the company has market growth opportunities and a trend of increasing demand for medical devices, but is faced with the threat of intense competition and complex regulations. Based on the SWOT analysis, a strategy is formulated that maximizes strengths and opportunities while minimizing weaknesses and threats. This study provides a strategic basis for company management to face competition and strengthen its position in the pharmaceutical and medical device distribution market.